Summarizing Malayalam News Articles Using Topic Modeling - Anjana T G
People in this era are overloaded by their daily exposure to large amount of information. The highlights of an article provide the readers with a gist of the story quickly. Summarization is one of the efficient techniques to bring out significant compression to the original news articles. Summaries are a way to distil the essence of a reading to its most important points. This work aims to summarize a Malayalam news article. Here topic modeling is used to enhance the quality of the generated summary. The topics produced by topic modeling techniques are clusters of similar words. By using these topics as the keywords, a more relevant and informative summary can be generated.